Genetic diversity in exotic oat germplasm & resistance against barley yellow dwarf virus - Jan, Shazma Firdous (Saudi J Biol Sci, 2020)
Oat (Avena sativa L.) is an important fodder crop of Pakistan, though with low productivity. The present study was conducted to evaluate the performance and genetic diversity of exotic oat germplasm, with emphasis on cereal yellow dwarf virus resistance. A total of 16 exotic line (introduced from Aarhus University Denmark) and 1 local line (provided by The University of Agriculture Peshawar), were grown during the season 2017–18 in Completely Randomized Block Design with three replications across two locations of Khyber Pakhtunkhwa i.e., Peshawar and Kohat. Field testing enabled to collect the data on BYDV incidence, BYDV severity, aphid infestation, plant height, leaf area, panicle length, panicle weight, spikelets per panicle, 1000 grain weight (g), grain yield (g), biological yield (g) and harvest index (%). Prevalence of BYDV was variable across location and over time. Six weeks data showed high disease pressure at Peshawar (85%), with SA-O-01 genotype having AUDPC value of 95%. Almost all the varieties showed less tolerance towards the Aphids attack. Line SA-O-15 showed the maximum 1000 grain weight (42.6 g) at Kohat, while SA-O-4 showed the maximum 1000 grain weight (60.7 g) at Peshawar. Line SA-O-05 (3634 g per (0.9 m(2)) plot) gave the maximum biological yield at Kohat station, while Line SA-O-01 gave the maximum biological yield (2517 g) at Peshawar. Mean grain yield for Kohat was recorded 0.155 g per (0.9 m(2)) plot while for Peshawar it was 0.231 g per (0.9 m(2)) plot. At Kohat line SA-O-10 produced the maximum grain yield (0.229 g), while line SA-O-12 produced the maximum grain yield at Peshawar (0.288 g). Molecular genotyping with a set of 4 RAPD primers revealed substantial diversity among17 oat lines. A total of 23 loci were amplified showing a high level of variations and polymorphism among the proposed lines. The maximum number of loci was recorded for GLA-04 (8), while the minimum number of loci was recorded for GLD-18 (4). Among the tested RAPD primers the maximum gene diversity (0.529) was recorded for loci GLA-03B230, GLA-04B130, GLA-04B300, GLB-05B150 and GLA-18B100 while the minimum (0.118) genetic diversity was recorded for loci GLA-03B600, GLB-05B330 and GLA-18B500. A clear divergence was found between most of the exotic oat lines. The observed genetic diversity in exotic oat germplasm and its resistance towards Barley Yellow Dwarf virus could be useful for oat genetic improvement and broadening the genetic background of cultivated oat germplasm.